A novel KCNQ1 nonsense variant in the isoform-specific first exon causes both jervell and Lange-Nielsen syndrome 1 and long QT syndrome 1: a case report - Motoi Nishimura; Marehiko Ueda; Ryota Ebata; Emi Utsuno; Takuma Ishii; Kazuyuki Matsushita; Osamu Ohara; Naoki Shimojo; Yoshio Kobayashi; Fumio Nomura (BMC, 2017)
Abstract Background According to previous KCNQ1 (potassium channel, voltage gated, KQT-like subfamily, member 1) gene screening studies, missense variants, but not nonsense or frame-shift variants, cause the majority of long QT syndrome (LQTS; Romano-Ward syndrome [RWS]) 1 cases. Several missense variants are reported to cause RWS by a dominant-negative mechanism, and some KCNQ1 variants can cause both Jervell and Lange-Nielsen Syndrome (JLNS; in an autosomal recessive manner) and LQTS1 (in an autosomal dominant manner), while other KCNQ1 variants cause only JLNS. The human KCNQ1 gene is known to have two transcript isoforms (kidney isoform and pancreas isoform), and both isoforms can form a functional cardiac potassium channel. Case presentation Here, we report a novel nonsense KCNQ1 variant causing not only JLNS, but also significant QTc prolongation identical to RWS in an autosomal dominant manner. Our case study supports that haploinsufficiency in the KCNQ1 gene is causative of significant QTc prolongation identical to RWS. Interestingly, the nonsense variant (NM_000218.2:c.115G > T [p.Glu39X]) locates in exon 1a of KCNQ1, which is a kidney-isoform specific exon. The variant is located closer to the N-terminus than previously identified nonsense or frame-shift variants. Conclusion To the best of our knowledge, this is the first report showing that a nonsense variant in exon 1a of KCNQ1, which is the kidney-isoform specific exon, causes JLNS. Our findings may be informative to the genetic pathogenesis of RWS and JLNS caused by KCNQ1 variants.